Evaluation of tahfiz al-Quran curriculum in Nusantara / Muhammad Hafiz Saleh - Muhammad Hafiz , Saleh (2019)
This study aims to evaluate the tahfiz al-Quran curriculum in Nusantara by adopting the Discrepancy Evaluation Model (Malcolm Provus 1971) and Tahfiz al-Quran Theory (Syukri & al-Auratani 2003). The objectives of this study are (i) to design the tahfiz al-Quran curriculum standards, which consist of three main aspects: the objectives of the tahfiz al-Quran curriculum, the process of memorising the Quran and the hafiz al-Quran standards; (ii) to evaluate the tahfiz al-Quran curriculum in terms of the tahfiz al-Quran curriculum objectives, the process of memorising the Quran and the hafiz al-Quran standards in selected tahfiz al-Quran institutions in Nusantara; (iii) to analyse the discrepancy between the designed tahfiz al-Quran curriculum standards with the actual performance achieved by the selected tahfiz al-Quran institutions; and (iv) to design a standard Tahfiz al-Quran curriculum model. This study involves four phases, which are: (a) the design phase, which uses document analysis and the Fuzzy Delphi Method (FDM) involving fourteen experts; (b) the evaluation phase, which uses a questionnaire and involves 260 respondents; (c) the discrepancy phase, which compares the designed tahfiz al-Quran curriculum standards with the actual performance achieved by the selected tahfiz al-Quran institutions; and (d) the development of a standard Tahfiz al-Quran curriculum model using the Nominal Group Technique (NGT), which involves fourteen experts in the field of tahfiz al-Quran. The questionnaire used in this study is reliable according to the Cronbach alpha test output, with the standardised item alpha being α = .953. This study developed a standard Tahfiz al-Quran curriculum model which consists of six objectives of the tahfiz al-Quran curriculum, thirty-five processes of memorising the Quran and twenty-nine hafiz al-Quran standards and found that the achievement of the selected tahfiz al-Quran institutions in terms of objectives and memorizing process were high and moderate. In terms of the hafiz al-Quran standards’ achievement, it was found to be moderate. The researcher found six discrepancies between the designed tahfiz al-Quran curriculum standards with the actual performance achieved by the selected tahfiz al-Quran institutions. At the end of the study, the researcher developed a standard tahfiz al-Quran curriculum model comprising six objectives of the tahfiz al-Quran curriculum, thirty five processes of memorising the Quran and twenty nine hafiz al-Quran standards that could serve as a guide for the tahfiz al-Quran curriculum development or as an evaluation tool for identifying the strengths and weaknesses of a tahfiz al-Quran curriculum.